Representation of a Physio-psychological Index Through Constellation Graphs - Mayumi, Oyama-Higa; Miao, Tiejun (Advances in Natural Computation, 2005)
Chaos theory was applied to analysis of the time series of plethysmograms under various human physio-psychological conditions. It found that the largest Lyapunov exponent could be used to characterize physio-psychological status. A visual representation method based on constellation graphs was developed to indexing temporal changes in the largest Lyapunov exponent. Changes of constellation angles were found to clearly characterizing variations of physio-psychological status in a series of experiments.